Metaheuristic-driven CatBoost models for accurate seepage prediction in heterogeneous earth-fill dams on permeable foundations - Mohamed Kamel Elshaarawy; Muhammad Zeeshan Khursheed; Badee Alshameri; Mohamed Maher Sayed Ahmed (Physics and Chemistry of the Earth, Parts A/B/C, 2026)

Dynamic response and seismic fragility of monopile foundations for offshore wind turbines considering pile-soil interaction - Xuefei Wang; Yifan Zhang; Yafei Tian; Badee Alshameri; Jiale Li (Ocean Engineering, 2026)

Modeling seismic risk and economic loss for urban sustainability: insights from a Gulf city - Abdullah Ansari; Issa El-Hussain; Yousuf Al-Shijbi; Ayed E. Alluqmani; Hajar Al-Qayoudhi; Yewuhalashet Fissha; Shima Albalushi; Badee Alshameri (Modeling Earth Systems and Environment, 2026)
This study delivers the first comprehensive microzonation-based seismic risk assessment for the Al-Seeb region in Muscat, Oman. It integrates geotechnical, structural, environmental, and socio-economic vulnerability factors using a Geographical Information System (GIS) based multi-criteria framework. The Analytic Hierarchy Process (AHP) was employed to systematically weight and integrate these indicators, ensuring an objective evaluation of their relative influence on overall seismic vulnerability. Moving beyond traditional methods, it translates microzonation data into spatially distributed Average Annual Loss (AAL) zones and estimates economic impacts through Loss Exceedance Curves (LEC) and Probable Maximum Loss (PML). By coupling detailed hazard zonation with building typologies and infrastructure exposure, the study develops an asset-level risk profile, revealing sharp spatial variations in seismic risk driven by site conditions and construction quality. The results serve as a vital planning tool for civil authorities, aligning with Oman Vision 2040 and United Nations Sustainable Development Goal (UN SDG) 11. The approach offers a scalable model for rapidly urbanizing Gulf cities such as Doha, Riyadh, Dubai, and Kuwait, providing a data-informed foundation for enhancing infrastructure resilience and strengthening disaster risk management strategies.